The Cuban hustle : culture, politics, everyday life - Fernandes, Sujatha (Duke University Press, 2020)
"In THE CUBAN HUSTLE Sujatha Fernandes analyzes Cuba's cultural expression, politics, and everyday life across the last thirty years, a critical period of immense change in Cuba. She illuminates the myriad ways in which ordinary Cubans have survived, hustled, and created alternative cultures since the collapse of the Soviet Union. These essays cover a range of topics-from hip hop to feminism to Facebook-- based in the author's deep knowledge of Cuba and access to a number of subterannean cultures. They look, in part, at the development of urban black cultures like hip hop; visual artists' response to the global marketing of Cuba; the Cuban response to 9/11; new cultures of documentary filmmaking; the Weekly Packet (the Cuban version of the internet, circulated on flash drives); children filmmakers in a Cuban rural town; the death of Fidel Castro; and a hairdressers' project for social change. Fernandes reveals a complex, alive nation whose multiple influences and range of visions for itself contrasts with the Western view of Cuba's unidirectional path towards capitalism. The volume is divided into three sections. "Cultures of the Special Period" looks at the emergence of dynamic youth cultures and social movements in the 1990s, as Cuba grappled with economic collapse and the government took on a siege mentality, clamping down on critical expression. In place of the openly confrontational art of the 1980s, artists and activists now sought to negotiate with state officials and penetrate state organizations. The second section, "Normalization: Netflix Meets the Weekly Package," covers the period when President Obama restored diplomatic ties with Cuba, as well as Cubans' engagement with new digital technologies. The last section, "Cuban Futures and the Trump Era," examines ongoing attempts to create social justice projects despite renewed hostilities from the United States, including reimposed travel and trade restrictions. Cuba maintains a culture of resistance, and Cubans show a remarkable ability to continually reinvent themselves under difficult circumstances"--